IMPLEMENTATION OF ECONOMIC ORDER QUANTITY (EOQ) AND OPTIMAL VALUE INVENTORY LEVEL TO IMPROVE CASH CONVERSION CYCLE (CASE STUDY: PT. WISMILAK INTI MAKMUR TBK.) (The Indonesian Journal of Business Administration, 2019)
PT. Wismilak Inti Makmur Tbk. is one of the biggest cigarette company in Indonesia. This company was established in 1962 at Surabaya. The current condition of this company has relative decreasing in the financial condition. However, this company has a problem with the value of Cash Conversion Cycle. Cash Conversion Cycle is an indicator that describes the ability of companies to convert their cash into goods or inventory to be sold or converted back into cash. By using the cash conversion cycle, it can measure how quickly and efficiently a company extracts cash from operations and we can find out how efficiently a company manages the operations. A short number means that the company has a positive cash cycle and is efficiently managing operations ,and the longer number indicates the negative cash cycle and uneffecient when managing the operation.Based on the issues that occurred with PT. Wismilak Inti Makmur, the condition of the company's cash conversion cycle is far longer than the average industry. This indicates that the management of company's working capital is not optimal when compared with the industry average. The high inventory value causes the high value of the average age of inventory. It is impacting on the calculation of the cash conversion cycle to become longer. Therefore, the author optimizes the value of inventory. The optimization using two methods which are the Economic Order Quantity (EOQ) and the Optimal Value Inventory Level. The results of the EOQ calculation, a company can minimize raw material based on the order period, which are 12 times a year. In one order, the company needed 667,823 kg of raw materials for the company's needs for 30 days. To overcome excessive demand while using the EOQ system, companies must consider the safety stock of these raw materials. From the calculation, a total of one order was obtained after the safety stock was added, namely 822,964 kg or equivalent to 36,484,733,485 rupiahs. Then, at the end of recording the balance sheet end of the year, inventory from raw materials is reduced become 36,484,733,485 rupiahs. The company's total inventory after using the EOQ system was 217,849,982,827 rupiahs, from the previous 652,607,842,394 rupiahs.Based on total inventory values after calculating the EOQ system, it shows significant changes. The average age of inventory decreased significantly to 82 days from 247 days. This decrease has an impact on the cash conversion cycle to 53 days compared to before using the EOQ method, which is 217 days.Therefore, the author recommend PT. Wismilak Inti Makmur to use the EOQ method to run its business. So, the company can improve company performance of working capital optimally.Keywords: Working Capital Management, Operations, Average Age of Inventory, Cash Conversion Cycle , and Economic Order Quantity (EOQ)